2009
DOI: 10.1074/jbc.m808090200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical Chromatin Looping and Transcription Factor Association on the Regulatory Regions of the p21 (CDKN1A) Gene in Response to 1α,25-Dihydroxyvitamin D3

Abstract: The nuclear receptor vitamin D receptor (VDR) is known to associate with three vitamin D response element (VDREs)-containing regions within the CDKN1A (p21) gene region. Here we show in MDA-MB453 breast cancer cells that the natural VDR ligand 1␣,25-dihydroxyvitamin D 3 causes cyclical transcription factor binding and chromatin looping of distal VDREs to the transcription start site (TSS) of the p21 gene, leading to cyclical accumulation of the p21 mRNA. At the chromatin level, association of the mediator prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 26 publications
7
86
1
Order By: Relevance
“…41 p21 contains three VDREs, and is known to be regulated by Calcitriol-induced cyclical chromatin looping. 42 In agreement with these reports, we found decreased expression of the p21 tumor suppressor gene in our breast cancer samples, as would be expected in the context of an inactive Calcitriol pathway (see Fig. 6).…”
Section: Discussionsupporting
confidence: 80%
“…41 p21 contains three VDREs, and is known to be regulated by Calcitriol-induced cyclical chromatin looping. 42 In agreement with these reports, we found decreased expression of the p21 tumor suppressor gene in our breast cancer samples, as would be expected in the context of an inactive Calcitriol pathway (see Fig. 6).…”
Section: Discussionsupporting
confidence: 80%
“…It can also be inferred from this hypothesis that the mobilization dynamics of the proteins recruited by ER on chromatin (7,8) may be at least partly responsible for the dynamic property of ERBS-promoter physical contacts. Such a process was evidenced in the case of the CDKN1A gene promoter placed under the transcriptional control of another nuclear receptor, the vitamin D3 receptor (VDR) (72). Accordingly, our kinetic 3C dissection of the three-dimensional reorganization of the TFF cluster indicates that all interactions between ERBSs and gene promoters already exist in the absence of E2.…”
Section: Discussionmentioning
confidence: 90%
“…Previous results have shown that class-IIa HDACs can control CDKN1A expression (Liu et al, 2009;Mottet et al, 2009;Saramaki et al, 2009;Wilson et al, 2008); however, the mechanisms involved are debated. MEF2-binding sites are present in the genomic regions surrounding CDKN1A.…”
Section: Discussionmentioning
confidence: 99%